CD Multimedia Interactive to Teach Philosophy of Islamic Education for Sophomore in IAIN Tulungagung - Abd. Aziz (Ta'allum: Jurnal Pendidikan Islam, 2018)
The development of technology and information today, especially in media information and communication can produce pattern of thinking and attitude to be a good progress. Moreover, with the rapid develop of technology right now, the world of education also join to plays a role in the process of utilizing of emerging technologies. In this case, utilizing the learning technology media to benefit optimally is useful for education process, as well as the teacher’s role that also needed for teaching and learning philosophical of Islamic education. The students are able to understand the material about philosophy and to hone the students’ thinking happily and motivated if the teacher teach them using multimedia interactive. Since this learning strategy can guide the students completely in order to master the philosophy material quickly. This multimedia Interactive help the students to learn and understand the materials of philosophy which can operate by computer. Those CD interactive program made by compound some materials in the form of film, moving picture, animation, and games. Therefore, the students are able to understand Philosophy of Islamic Education by utilizing the virtual picture of material which was packed in compact disc form even can be operated with computer or laptop.